Heart Transplantation in Belarus - Yu. P Ostrovsky; L. V. Rachok; I. A. Grebenyuk; E. K. Kurlyanskaya; A. V. Valentyukevich; O. G. Chernookiy; L. G. Shestakova; V. S. Khudnitskaya; T. A. Dubovik; M. G. Kolyadko (Transplantation and artificial organs, 2020)
Objective. To evaluate the effectiveness of the treatment of patients with end-stage heart failure.Materials and methods. In total for the period from 2009 to 2019, 3038 potential recipients of donor heart were examined, of which 22% were put on a waiting list of transplantation. Orthotopic heart transplantation was performed in 326 patients, which accounted for 40% of the total number of patients on the waiting list for a ten-year period.Results and discussion. During the period from 2009 to 2019, orthotopic heart transplantation in Belarus on the basis of the Scientific-Practical Center «Cardiology» was performed for 326 patients with terminal heart failure. The preference was given to the biatrial technique (89%), only 30 patients were operated on using the bicaval technique (11%). The duration of artificial blood circulation was 250 + 24 min. The patient’s stay after heart transplantation in the intensive care unit and reanimation was 9 + 3 days, while the duration of artificial respiration was 10 + 6 hours on average. The hospital period averaged 23 + 6 days. The average for 10 years the hospital mortality rate was 8.4%, and in the period from 2016 to 2019 did not exceed 7.2%. The dynamics of survival rates are presented graphically in the diagram.Findings. Currently, the achievements of transplantology have allowed us to achieve some success in the struggle for the lives of patients, which a few decades ago, medicine could only dream of. Today, the team of cardiac surgeons and cardiologists is faced with the task of finding methods to ensure the longest life expectancy of the donor organ by reducing the risk of various complications, as well as developing new technologies that will maximize the life expectancy of patients with terminal heart failure in anticipation of an optimal donor heart.